Quiet standing postural control variables in subacute stroke: associations with gait and balance, falls prediction and responsiveness. Issue 8 (10th April 2023) - Bower, Kelly J.; Thilarajah, Shamala; Williams, Gavin; Pua, Yong-Hao; Tan, Dawn; Clark, Ross A.
Abstract: Purpose: To examine the construct validity, predictive validity and responsiveness of standing centre of pressure variables in subacute stroke. Materials and methods: Seventy-nine ambulatory individuals were assessed before inpatient rehabilitation discharge and three months later. Measures were: gait speed (6-metre walk), dynamic balance (step test), and quiet standing (Wii Balance Board). Centre of pressure speed, amplitude, standard deviation, root mean square, wavelet decomposition, and detrended fluctuation analysis were examined. Falls data were collected over a 12-month period post-discharge. Results: Moderate strength correlations ( r  = −0.505 to −0.548) with gait speed and step test scores were shown for 3/26 centre of pressure variables (mediolateral speed, low and moderate frequency wavelet). Twenty-two participants fell and the prediction was significant for gait speed and step test (IQR-odds ratio (OR) = 4.00 & 3.21) and 3/26 centre of pressure variables (mediolateral low-frequency wavelet: IQR-OR = 2.71; mediolateral detrended fluctuation analysis: IQR-OR = 3.06; anteroposterior detrended fluctuation analysis: IQR-OR = 2.71). Significant changes over time occurred for gait speed and step test scores and 20/26 centre of pressure variables. Conclusions: Standing centre of pressure variables have limited validity to reflect dynamic balance and falls risk after stroke. Frequency and complexity measures warrant further exploration. Implications for rehabilitation: Our findings indicate that quiet standing centre of pressure variables have limited validity to reflect dynamic balance tasks and predict falls after stroke. The mediolateral and higher frequency variables may be more strongly recommended than the commonly used total centre of pressure speed measure. Measures of signal frequency and complexity may provide insight into postural control mechanisms and how these change over time following stroke.